Crosstalk between c-Myc and ribosome in ribosomal biogenesis and cancer - Dai, Mu-Shui (2008)
Protein production is driven by protein translation and relies on ribosomal biogenesis, globally essential for cell growth, proliferation, and animal development. Deregulation of these sophisticated cellular processes leads to abnormal homeostasis and carcinogenesis. Thus, their tight regulation is vitally important for a cell to warrant normal growth and proliferation. One newly-identified key regulator for ribosomal biogenesis and translation is the oncoprotein c-Myc, whose aberrantly excessive level and activity are highly associated with human cancers, too. Recently, we have shown that ribosomal protein L11 functions as a feedback regulator of c-Myc. Hence, in this review, we will provide some prospects on the interplay between c-Myc and ribosomal proteins during ribosomal biogenesis and discuss its implications in cancer.